Patients' knowledge and attitudes towards health education: Implications for primary health care services in Saudi Arabia - Mohammed S Alnaif; Saad A Alghanim (Wolters Kluwer Medknow Publications, 2009)
Objectives: To assess health educational activities in primary health care centers in Riyadh City. Methods: The data were collected through a self-administered questionnaire directed at adult patients who attended primary health care centers from February - April 2006, in Riyadh City. Out of the 750 patients who were selected randomly, 569 (75.9%) successfully completed the questionnaire. The data collected were on a set of variables including socio-demographic characteristics, health-related variables, source of health knowledge and patients' attitudes towards a number of health-related aspects. Data were presented and analyzed in a descriptive fashion. Results: Only 20% of PHC patients had received health education in the past twelve months. The majority of respondents identified TV and friends/relatives as the main sources of their health education. A considerable percentage of the patients with chronic conditions lacked knowledge about their illnesses. The results indicate that the deficiency in knowledge was the result of some of the socio-demographic characteristics of respondents. Conclusion: There is an urgent need to review and evaluate health education programs conducted in PHC centers. Special emphasis should be placed on health education activities for those living with chronic health conditions.